Detection and quantification of sub-micromolar concentrations of aqueous anions using infrared spectroscopy and mass spectrometry - Hebert, Gretchen N., author; Strauss, Steven H., advisor; Fisher, Ellen, committee member; Maciel, Gary E., committee member; Crans, Debbie C. committee member; Reardon, Kenneth F., committee member (Colorado State University. Libraries, 2004)
Two different techniques, electrospray ionization mass spectrometry (ESIMS) and attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, were used for the detection and quantification of low concentrations of aqueous anions. Some of these anions, including perfluoroalkanesulfonates (PFAS–), perchlorate, phosphonates, and cyanide, are of interest given that they may cause human health problems and/or persist in the environment. Two ESIMS methods, standard addition and direct-injection, are presented for the quantification of aqueous PFAS– anions, specifically perfluoro-noctanesulfonate (PFOS–). A concentration of 0.6 ± 0.1 μM PFOS– was quantified in groundwater from a well at a fire-training area at Wurtsmith Air Force Base (WAFB), Oscoda, MI using the method of standard additions. Using the direct-injection method, detection down to 6 nM PFOS– was successful and linear calibration curves were determined ranging from 0.01 to 5 μM PFOS–. The direct-injection method was used to quantify PFAS– anions in the groundwater from wells at WAFB. The concentrations of PFAS– anions determined using the standard addition method were the same to within experimental error as those determined using the direct-injection method. It is probable that the observed PFAS– anions were components of some of the fire-fighting materials, including aqueous film-forming foams (AFFFs), used at this site until 1993. Concentrations of PFAS– anions up to 0.6 μM were found in the groundwater despite a minimum of five years since active fire-fighting activity ceased at WAFB. This is the first reported example of the persistence of PFAS– anions in groundwater over a period of several years. A new ATR-FTIR method was developed for the detection and identification of sub-micromolar concentrations of aqueous polyatomic anions. The technique involves coating the surface of an ATR crystal with a thin-film coating of an organometallic ion-exchange extractant, which enabled anion detection limits to be lowered up to 23,000-fold below those achieved using the same commercially available ATR-FTIR spectrometer with an uncoated ATR crystal. A four-coordinate nickel (II) complex was used as a ligand-exchange reagent to detect cyanide. All of the other anions were detected using the nitrate or the chloride salt of a tetraalkylated ferroeenium cation. Detection limits for perchlorate, chlorate, trifluoromethanesulfonate, perfluoro-n-hutanesulfonate, perfluoro-n-oetanesulfonate, pinacolylmethylphosphonate, and cyanide were 0.03, 0.2, 0.05, 0.07, 0.06, 0.7, and 0.09 μM, respectively, using coated ATR crystals. Detection limits were defined as the concentration for which the signal-to-noise ratio was ≥3 ± 1 for a 10-minute analysis time. Linear calibration curves based on d(absorhance)/dt, which is related to the rate of anion exchange, were established in the 0.04-30 μM range. Several complex matrixes, including synthetic tap water, simulated seawater, and hydroponic fertilizers, were examined. Using the method of standard additions, trace quantities of perchlorate were detected in some hydroponic nitrate fertilizers where the nitrate to perchlorate concentration ratios were as high as 9,000. The concentrations of perchlorate detected in these fertilizers were the same within experimental error as those determined by three other techniques performed in three different laboratories. This simple ATR-FTIR detection/quantification method afforded good reproducibility with relatively fast (10-minute) detection times.
Keywords: analytical chemistry; organic chemistry